Effect of plasmin on casein hydrolysis and textural properties of rennet-induced model cheeses. (March 2023) - Cai, Huifang; Bijl, Etske; Scholten, Elke; Sala, Guido
Graphical abstract: Highlights: Plasmin hydrolyzed β- and αs2 -CN during initial proteolysis. Textural parameters did not significantly change during initial proteolysis. After 40–60 % CN was hydrolyzed, Young's modulus and hardness started to decrease. Rapid decrease in resilience and cohesion was related to further hydrolysis of CN. Large hydrolyzed fragments were important to the network strength. Abstract: Plasmin plays an important role in casein hydrolysis during cheese ripening, which may influence the properties of the casein network and the texture of the final product. In view of this, the relation between plasmin-induced casein hydrolysis and textural changes of cheese during ripening was investigated in this study. Four batches of model cheese with different concentrations of added plasmin (0, 0.4, 0.6 and 1.0 μL/g milk) were prepared, and were stored for 12 weeks at 16 °C. During this period, plasmin activity, casein hydrolysis, textural properties and other compositional characteristics (pH, dry matter) were determined. Our results show that the addition of plasmin had significant effect on both the degree and the pattern of proteolysis. As a result, cheeses with different plasmin content showed different textural properties. With increased plasmin concentration, Young's modulus, hardness, resilience and cohesion decreased, while brittleness increased. All textural properties showed linear relations with the degree of casein hydrolysis, and logarithmic relations with the percentage of intact casein fractions. At the beginning of ripening, only slight changes in textural properties were found, although a substantial part (40–60 %) of the casein fractions was already been broken down. When ripening progressed, ongoing proteolysis significantly weakened the protein network and consequently led to noticeable textural changes. Model cheeses became softer, more brittle and less elastic. The knowledge gained from this study provide new insights in the changes of different textural parameters of model cheese. This will help to optimize the existing products and create new ones.